Tea Time at Wonderland. Domestic models and family relationships over the looking glass - Maria Teresa Trisciuzzi (Firenze University Press, 2017)
The character of Alice, the English "dream child" of the second half of the 19th century, was born from the fantasy of Charles Lutwidge Dodgson, best known with the nom de plume Lewis Carroll. In her travels Alice does not look for a new fami-ly to substitute hers, but for her own freedom of being and knowing herself through an initiation path.  Alice - Alice's Adventures in Wonderland (1865) and Through the Looking-Glass and What Alice Found (1871) - is a masterpiece of nonsense only on its surface, because actually it has an underground, which makes it able to see from a child's point of view and to understand what being a child means in a world ruled by petulant, unreliable and rude adults. Alice repre-sents the great metaphor of the escape; she leaves her family through escaping to somewhere else, which brings her to an inner adventure in the depths of being. In the novels of Carroll the reader can find everyday life themes, such as the domes-ticity, being a mother and taking care, but in an upside-down and paradoxical way.